2011
DOI: 10.1287/mksc.1100.0626
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Model of Sponsored Search Advertising

Abstract: Sponsored search advertising is ascendant--Forrester Research reports expenditures rose 28% in 2007 to $8.1 billion and will continue to rise at a 26% compound annual growth rate [VanBoskirk, S. 2007. U.S. interactive marketing forecast, 2007 to 2012. Forrester Research (October 10)], approaching half the level of television advertising and making sponsored search one of the major advertising trends to affect the marketing landscape. Yet little empirical research exists to explore how the interaction of variou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
112
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(114 citation statements)
references
References 52 publications
2
112
0
Order By: Relevance
“…A myriad of researchers have turned to SSA data to uncover new insights about consumer search (Ghose and Yang, 2009;Rutz and Bucklin, 2011), choice and related purchasing behaviors (Jeziorski and Segal, 2009;Yang and Ghose, 2010;Agarwal et al, 2011) and advertiser/search engine strategies (Animesh et al, 2009;Yao and Mela, 2011;Rutz et al, 2012). Many of these papers have used random utility models to study the effect of ad position, keyword length, presence or absence of brand name, etc.…”
Section: Introductionmentioning
confidence: 99%
“…A myriad of researchers have turned to SSA data to uncover new insights about consumer search (Ghose and Yang, 2009;Rutz and Bucklin, 2011), choice and related purchasing behaviors (Jeziorski and Segal, 2009;Yang and Ghose, 2010;Agarwal et al, 2011) and advertiser/search engine strategies (Animesh et al, 2009;Yao and Mela, 2011;Rutz et al, 2012). Many of these papers have used random utility models to study the effect of ad position, keyword length, presence or absence of brand name, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have studied existing Web-search-based advertising networks (e.g., Google's ad market) [15,32,39], prediction markets run by Google, Ford and others [5], and have used "estimated prices" [17] from Google's Traffic Estimator Tool [23] (similar to our suggested bids) as a mechanism for understanding the network. Noti et al [29] demonstrated that bidders with some explicit knowledge during an initial learning phase can bid with better valuations than those without such knowledge; this implies that suggested bids can provide useful guidance for bidders.…”
Section: Related Workmentioning
confidence: 99%
“…Using a sample from a week's worth of data across all keywords on Bing, other work [4] showed how to optimize linear combinations of the stakeholder utilities, showing that these can be tackled through a GSP auction with a per-click reserve price. There has also been much work proposing new models for conducting online auctions [19,20,28,39].…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…One exception is Yao and Mela (2010), who make the problem tractable by looking at a hybrid auction mechanism developed for an individual website and suggest that dynamics are important in understanding firm bidding behavior. Another question addressed by academics is how the position of a search ad affects its performance.…”
Section: Search Advertisingmentioning
confidence: 99%